Strategi Pengembangan dan Penataan Kawasan Permukiman Kumuh Kota Pekanbaru - Zahidah Dela Lathifah A.R., Wirdatul (Journal of Comprehensive Science, 2024)
This research aims to analyze the development strategy and arrangement of slum areas in Pekanbaru City. The problem of slums in this city is increasingly urgent due to rapid population growth and uncontrolled urbanization. The research method includes a qualitative approach with a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis technique to identify internal and external factors that affect the arrangement of slum areas. This research uses the development strategies theory of Richard Rumelt. The results show that effective strategies include empowering the community and strengthening the role of Government, optimizing land use, and improving access to basic infrastructure. It is expected that with these strategies, the quality of life of people in slum areas can improve and create a habitable, sustainable, and integrated settlement environment with overall city planning. This research provides policy recommendations relevant to the local Government to overcome the problems of slum areas in Pekanbaru, emphasizing the importance of community involvement.